Auditing: where are the risks? - RAZUMOVAK. М. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2025)
The article explores the main risks inherent in audit activity, in particular in the field of financial monitoring, quality management system and risk assessment in the audit process, related to financial reporting. Emphasizing financial monitoring, the author systematizes the risks that may arise when accepting a client and a task: risks associated with the geographical location of the client or his representatives, by type of client, by the type of services provided to him (cash settlements, transactions with securities, insurance payments, and others). The study demonstrates that that systematized risks in the field of financial monitoring make it possible to identify clients and help audit firms comply with the requirements of legislation to prevent the legalization of proceeds of crime. It is proposed to pay special attention to the risks of distortion of financial statements, which affect the opinion in the auditor’s report. The author divides the actions in response to the assessed risks into general actions aimed at developing an audit strategy and plan; and segmented actions. Segmented activities are audit procedures aimed at specific assertions of financial statements, defined in the audit plan and performed to collect audit evidence. The article has practical value for auditors, heads of audit firms, as well as financial monitoring specialists, as it contains examples of risk scenarios and recommendations for their minimization. The presented results of the study contribute to the formation of the auditor’s professional judgment and the improvement of the quality of audit services in the conditions of strengthening regulatory requirements.